PEMETAAN DAERAH RAWAN PENYAKIT DEMAM BERDARAH DENGUE (DBD) DI KOTA BANDUNG MENGGUNAKAN APLIKASI QGIS - Jesa Nuhgroho; Tris Eryando; Martya Rahmaniati; Deny Yudhistira (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Dengue Hemorrhagic Fever (DHF) is a viral disease spread by a vector, Aedes Aegypti mosquitoes. This study aims to map the distribution of high vulnerability areas in Bandung City. The data used are secondary data from the 2021 District Health Office and 2022 the Central Agency of Statistics (BPS) from 30 sub-district reports in Bandung City. Map of Bandung City obtained from the Geospatial Information Agency via the website tanahair.indonesia.go.id. DHF case data and data that have a direct influence on the natural development of mosquitoes, including rainfall, air humidity, and population density are scored and classified. Then the data is assessed and analyzed to produce vulnerability level zones using the QGIS 3.28.0 application. The result shows that there are 5 sub-districts with high vulnerability level, sub-districts with medium vulnerability level, and 15 sub-districts with low vulnerability level. The five sub-districts with high vulnerability are Antapani, Bojongloa Kaler, Cibeunying Kidul, Kiaracondong, and Sukajadi sub-districts. Knowing the distribution of dengue-prone areas, it is hoped that it will make it easier for the Bandung City Health Service to take preventive measures and handle DHF cases by prioritizing sub-districts with a high level of vulnerability. The government is expected to increase community participation in programs to prevent and control DHF incidents in each sub-district. In addition, it is hoped that further research will examine other environmental factors and societal behavior factors that lead to the vulnerability of DHF cases so that the DHF disease control program in Bandung City is more specific, especially considering the characteristics of each region.